Perovskite solar cells based on hole-transporting conjugated polymers by direct arylation polycondensation. (9th July 2018) - Li, Wei; Mori, Takehiko; Michinobu, Tsuyoshi
Abstract: Abstract : Direct arylation polycondensation (DArP) is an emerging synthetic method of producing conjugated polymers in an environmentally benign and cost-effective manner. We now report the synthesis of hole-transporting conjugated polymers, namely, DPP-OMe ( M n = 7.9 kg/mol) andDPP-F ( M n = 12.6 kg/mol), under microwave-assisted DArP conditions. These two polymers and the previously synthesized3, 6-Cbz-EDOT were evaluated as hole-transporting materials in mesoscopic perovskite solar cells.3, 6-Cbz-EDOT synthesized by DArP exhibited higher hole mobility and better photovoltaic properties than that synthesized by the Stille polycondensation. Moreover, chemical dopants improved the short-circuit current density ( J sc ) and fill factor.